ANALISIS DESAIN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI SMA N 3 KOTA BENGKULU - Yenni Pusvita Dewi; Desy Eka Citra Dewi (STKIP Subang, 2024)
The purpose of this research is to analyze the structure and content of the curriculum in the subject of Islamic Religious Education and Character Education at SMA N 3 Kota Bengkulu, which is one of the supporting factors for the achievements attained by SMA N 3 Kota Bengkulu. The research method used is qualitative analysis that examines information sources in the form of documents related to the PAI curriculum at SMA N 3 Kota Bengkulu. The results of this study indicate that the Islamic Education and Character Education curriculum at SMA N 3 Kota Bengkulu is developed by PAI and BP teachers in order to create effective learning and achieve the goals, vision, and mission established by SMA N 3 Kota Bengkulu. The content of the development of the PAI and BP curriculum at SMA N 3 Kota Bengkulu includes 1) the objectives of Islamic education, 2) learning materials, 3) methods, 4) evaluations used, and 5) religious activities available at SMA N 3 Kota Bengkulu.